The Effectiveness of Familiar Auditory Sensory Training on Improving Glasgow Coma Scale Scores in Patients with Decreased Consciousness - Nada Rizky Nur Hanifah (Politeknik Kementerian Kesehatan Banjarmasin, 2026)
Decreased consciousness is a critical neurological condition requiring timely intervention to support brain recovery. Familiar Auditory Sensory Training (FAST), which uses personalized familiar sounds, is a promising non-pharmacological approach that activates cognitive and emotional pathways even in low-consciousness states. This quasi-experimental study used a pretest-posttest control group design with 46 participants, determined via G*Power (power = 0.75, effect size = 0.8). Glasgow Coma Scale (GCS) scores were assessed before and after the intervention using standardized observation sheets. Data were analyzed using the Wilcoxon Signed Rank Test. Results showed a significant improvement in the intervention group, with GCS scores rising from an average of 11.70 to 13.52. In contrast, the control group showed only a minimal increase, from 12.17 to 12.26. These findings indicate that FAST effectively enhances consciousness levels in patients with impaired awareness. As a safe, simple, and non-invasive method.